2019
DOI: 10.1136/bmjgh-2019-001806
|View full text |Cite
|
Sign up to set email alerts
|

Integrated prevention and management of non-communicable diseases, including musculoskeletal health: a systematic policy analysis among OECD countries

Abstract: IntroductionDevelopment and implementation of appropriate health policy is essential to address the rising global burden of non-communicable diseases (NCDs). The aim of this study was to evaluate existing health policies for integrated prevention/management of NCDs among Member States of the Organisation for Economic Co-operation and Development (OECD). We sought to describe policies’ aims and strategies to achieve those aims, and evaluate extent of integration of musculoskeletal conditions as a leading cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 41 publications
0
76
0
Order By: Relevance
“…All these initiatives offer direct and indirect opportunities to support MSK health care. However, the horizon for improvement in MSK health through national health policy for NCDs remains challenging [7,63]. Linked to SDG 3.4, global performance and monitoring targets for NCDs are principally aligned with mortality reduction for cancer, diabetes, respiratory conditions and cardiovascular disease, leaving less flexibility for prioritisation of MSK health, thereby offering fewer opportunities for governments to support necessary reform efforts for MSK health care [82].…”
Section: By 2030 Reduce the Global Maternalmentioning
confidence: 99%
See 1 more Smart Citation
“…All these initiatives offer direct and indirect opportunities to support MSK health care. However, the horizon for improvement in MSK health through national health policy for NCDs remains challenging [7,63]. Linked to SDG 3.4, global performance and monitoring targets for NCDs are principally aligned with mortality reduction for cancer, diabetes, respiratory conditions and cardiovascular disease, leaving less flexibility for prioritisation of MSK health, thereby offering fewer opportunities for governments to support necessary reform efforts for MSK health care [82].…”
Section: By 2030 Reduce the Global Maternalmentioning
confidence: 99%
“…The WHO Package of Essential Noncommunicable Disease Interventions for Primary Health Care in Low Resource Settings is also focussed on heart disease, stroke, cardiovascular risk, diabetes, cancer, asthma and chronic obstructive pulmonary disease [83] and policy initiatives in LMICs have historically overlooked MSK health [66]. In a recent systematic analysis of health policies focusing on integrated prevention or management of NDCs among member states of the Organisation for Economic Co-operation and Development, most countries had policies with targets for cancer (83%), cardiovascular disease (77%), diabetes (77%), respiratory disease (63%) and mental health (63%), while only 50% of countries had policies with an explicit focus on MSK health and/or pain [63]. Nonetheless, many of the proposed activities across the policies were relevant to improving MSK function, potentially offering opportunity for improvement.…”
Section: By 2030 Reduce the Global Maternalmentioning
confidence: 99%
“…MSK conditions are leading causes of work disability everywhere, yet they do not feature prominently on national health policy or research agendas. A review of system policies for prevention and management of non-communicable diseases among OECD countries found that in spite of the large societal burden MSK conditions did not feature prominently [123], and a recent study from Denmark showed that in spite of back and neck pain being the most burdensome conditions in terms of years lived with disability, only 0.88% of national health research budgets were spent on identifying effective prevention and treatment strategies [124] e and that included research related to the workplace. Thus, the first call to action in a research agenda regarding MSK conditions everywhere is to call on governments, NGOs, companies, foundations and everyone else involved in research funding to prioritise funding of research related to all aspects of MSK conditions and in particular as they relate to the workplace and to work disability.…”
Section: Research Agendamentioning
confidence: 99%
“…65 A high level of data is available for a significant portion of the population in the developed nations because of integrated healthcare systems in these countries. 105 Highly committed international initiatives are required to enhance data collection in LMICs. 106 However, prospective data collection requires a lot of time, effort and investment.…”
Section: International Initiatives To Boost Data Collectionmentioning
confidence: 99%